(3SHjd GdQTGO Edi Mce GdJbdjO hGdELJgGOs - (3jMji Hf GdeWgQ Hf ESeGYjd,J (B1268 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdSDGd GdPi ChQOg GdMbjQ ai Vef LhGH SDGdGJ hQOJ Ydi efgG eG jJYdb HGdJbdjO , hde jMVQfi MGd JMQjQg TF , aSCdfi HYV Cgd GdYde Cf CQbe Ydjg eG jXgQ di s
(3BNQgG (B:s
(3hEdG hbY ai hQWI ef MjK dGjTYQ gPG hef cTa Yf bdHg GdZWGA UGQ ai faSg efhQkG eJHhYkG hef CZdb Ydi faSg CHhGH GdaJM de jMX HWGFd hGddg jgOi hEdi gfG GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs